When States Align Social Welfare Programs: Considering the Child Support Income Exclusion for SNAP. (18th September 2020) - Heflin, Colleen M.; Lopoo, Leonard M.; Mackenzie‐Liu, Mattie
Abstract : Objective: In the United States, state social services rarely coordinate across departments, a practice that could both increase receipt and reduce administrative burden. The purpose of this article is to investigate the state‐level conditions associated with the adoption of policies that benefit participants in multiple social welfare programs, focusing on the case of the child support income exclusion for SNAP benefit eligibility calculations. Methods: Using annual data for each of the states (including the District of Columbia), we estimate multiple analyses to test three hypotheses regarding which factors are associated with policy adoption. Results: We find that collaboration across social programs is more likely as state income tax revenues increase and when administrative costs are lower. Conclusions: Our findings suggest that state revenue and administrative costs are associated with state interagency alignment but find only weak evidence that political ideology is a factor.